Paracoccidioides HSP90 can be found in the cell surface and is a target for antibodies with therapeutic potential - Moura, Ágata Nogueira D’Áurea (2020)
Paracoccidioidomycosis (PCM) is one of the most frequent systemic mycoses in Latin America. It affects mainly male rural workers in impoverished regions, and the therapy can last up to two years or use drugs that are very toxic. Given the need for novel safe and effective approaches to treat PCM, we have been developing monoclonal antibodies (mAbs) that could be used not only to block specific fungal targets, but also modulate the host’s antifungal immunity. In this work we show the generation of and promising results with an mAb against Heat Shock Protein (HSP)90, a molecular chaperone that is an important virulence factor in fungi. Using recombinant Paracoccidioides lutzii (Pb01) and P. brasiliensis (Pb18) HSP90 proteins produced in E. coli, we immunized mice and generated polyclonal antibodies and an IgG1 hybridoma mAb. The proteins were very immunogenic and both the polyclonal serum and mAb were used in immunofluorescence experiments, which showed binding of antibodies to the yeast cell surface. The mAb successfully opsonized P. lutzii and P. brasiliensis cells in co-incubations with J774.16 macrophage-like cells. Our results suggest that this mAb could serve as the basis for new immunotherapy regimens for PCM.